Diaphragmatic gap repair using autografts: experimental study - Campos, Néstor C; Araújo, Raquel; Camacho, María del C; Martínez, Jorge; Villar, Miguel (Cirugía del Uruguay, 1973)
Twelve dogs, out 2 series of 6, underwent tho performance of a diaphragmatic opening comprising about 25 % of the left hemidiaphragm, which was repaired utilizing grafts of their own skin and aponeurosis of the tensor of the fascia lata. The paper contains the results which indicate that both proc.dures are adequate, though the grafting of skin ressults in more adhesions and inflamatory elements are 1nore numerous.